Risk Based Analysis for Evaluating of Inspection Scope at PLTGU Muara Karang - Dadang Rohmansyah; Suwarno Suwarno (IPTEK Journal of Proceedings Series, 2019)
Power plant operation and plant aging influence plant reliability, strategy, and cost maintenance of PLTGU Block 1 Muara Karang. Several approach has been done to increase maintenance effectiveness as well as reducing it cost. Nevertheless, other strategies are necessary to be further developed adopting best practices in industries. In this study, we used Risk Based Inspection (RBI) method to evaluate scope of inspection on equipment in the HRSG 1.1 Muara Karang. Equipment has been investigated are pressure vessel, heat exchanger tube, and piping. The number of equipment under investigated are 26, where 10 equipments included in the medium risk category and 16 equipments included in the low risk category. There are 2 equipments where the inspection time interval is ≤ 2 years i.e. high pressure superheater 1 & 2